DISEMINASI TEMUAN IDENTIFIKASI SURAT SUARA TIDAK SAH DAN IMPLIKASINYA TERHADAP PENDIDIKAN PEMILIH PADA PEMILUKADA KABUPATEN WONOGIRI TAHUN 2024 - Retno Eko Mardani Sutarto; Siti Fatimah; Aziz Widhi Nugroho; Aisyah Rukmi Widowati; Azahery Insan Kamil (JOSH: Journal of Sharia, 2026)
The 2024 simultaneous regional elections (Pilkada) represent a crucial milestone in Indonesia's democratization process, including in Wonogiri Regency, which is holding elections for the Governor and Deputy Governor of Central Java, as well as for the Regent and Deputy Regent. A crucial aspect in maintaining the integrity and legitimacy of elections is the validity of ballot papers. Invalid ballots often indicate problems with voter literacy, voting techniques, and the distribution of information related to voting procedures. This study aims to disseminate the results of the identification of invalid ballots in both elections, focusing on their categories, causes, and implications for the quality of local democracy. The method used was a qualitative descriptive analysis utilizing primary data from vote counting results at polling stations (TPS) and interviews with election organizers at the sub-district and village levels. The identification results showed that invalid ballots were generally caused by three main factors: technical errors by voters in voting (for example, marking more than one column), intolerable physical damage to the ballots, and forms of political protest through deliberate blanking or scribbling. Interesting findings indicate a correlation between voter education level and the number of invalid ballots, as well as significant differences between sub-districts. Disseminating the results of this study is crucial for providing input to the General Elections Commission (KPU) and the Elections Supervisory Agency (Bawaslu) in designing more effective voter education strategies. Furthermore, the findings of this study are expected to raise public awareness regarding the importance of understanding proper voting procedures. Thus, efforts to reduce the number of invalid ballots can contribute to improving the quality of democracy, transparency, and accountability of election administration in Wonogiri Regency in particular and Indonesia in general.